Impact of different front-of-package labeling models on food choices among residents in Shanghai, China: a randomized controlled trial - Sun, Zhuo; Chen, Xiao; Yu, Jiangyue; Lu, Wei; Shi, Zehuan; Huang, Kunyi; Shen, Liping; Ma, Wenqing; Mai, Shupeng; Song, Qi; Wang, Zhengyuan; Zang, Jiajie (Frontiers in Nutrition, 2025)
BackgroundIncreased convenience food consumption poses considerable public health concerns because of its high oil, salt, and sugar content. The World Health Organization endorses front-of-pack labeling (FOPL) as a strategy to enhance consumer choice toward healthier options. Despite their global adoption, the efficacy of various FOPL systems in China’s unique market remains unexplored. Here, we evaluated the impact of different FOPL models on the food purchasing behaviors of Shanghai residents.MethodsThis randomized controlled trial included 7,346 respondents, who were randomly assigned to one of four FOPL groups: Nutri-Choice (NC), Nutrition Information Panel (NIP), Comprehensive Nutri-Choice (CNC), and Warning Label (WL). An online questionnaire was used to collect the respondents’ demographic profiles. The sensory perceptions, nutritional ranking ability, and intention to purchase healthy foods of the respondents were evaluated using a simulated shopping experiment.ResultsIn total, 88.03% of the respondents supported FOPL use in China. Respondents completed the NC and WL questionnaires more quickly than the CNC or NIP questionnaire, with the NIP questionnaire taking the longest to complete (Z = 24.209, df = 3, p < 0.001). Sensory perception total approval rates were significantly higher for NC (57.01%), CNC (58.04%), and WL (57.77%) than for NIP (43.33%; χ2 = 112.958, df = 3, p < 0.001). Similarly, the total accuracy rate in the nutritional ranking was significantly higher for NC (69.94%) and CNC (72.45%) than for WL (55.44%) and NIP (32.99%; χ2 = 737.823, df = 3, p < 0.001). The purchasing intentions were the healthiest for CNC (83.10%), followed by NC (80.09%)—with both significantly outperforming NIP (75.11%) and WL (73.42%; χ2 = 63.360, df = 3, p < 0.001).ConclusionNC and CNC potentially improve consumers’ understanding of packaged food nutritional data, encouraging healthier purchasing decisions. Our results provide a scientific rationale for formulating and implementing an impactful FOPL initiative in China.